Training of resistance to proactive interference and working memory in older adults: a randomized double-blind study. (19th October 2015) - Loosli, Sandra V.; Falquez, Rosalux; Unterrainer, Josef M.; Weiller, Cornelius; Rahm, Benjamin; Kaller, Christoph P.
ABSTRACT: Background: Working memory (WM) performance is often decreased in older adults. Despite the growing popularity of WM trainings, underlying mechanisms are still poorly understood. Resistance to proactive interference (PI) constitutes a candidate process that contributes to WM performance and might influence training or transfer effects. Here, we investigated whether PI resistance can be enhanced in older adults using a WM training with specifically increased PI-demands. Further, we investigated whether potential effects of such a training were stable and entailed any transfer on non-trained tasks. Method: Healthy old adults ( N = 25, 68.8 ± 5.5 years) trained with a recent-probes and an n -back task daily for two weeks. Two different training regimens (high vs. low PI-amount in the tasks) were applied as between-participants manipulation, to which participants were randomly assigned. Near transfer tasks included interference tasks; far transfer tasks assessed fluid intelligence (gF) or speed. Immediate transfer was assessed directly after training; a follow-up measurement was conducted after two months. Results: Both groups similarly improved in PI resistance in both training tasks. Thus, PI susceptibility was generally reduced in the two training groups and there was no difference between WM training with high versus low PI demands. Further, there was no differential near or far transfer on non-trained tasks, neither immediately after the training nor in the follow-up. Conclusion: PI-demands in WM training tasks do not seem critical for enhancing WM performance or PI resistance in older adults. Instead, improved resistance to PI appears to be an unspecific side-effect of a WM training.